LESBI AKADEMIK POTRET RELIGIUSITAS MAHASISWI PERGURUAN TINGGI ISLAM - Muiz, Abdul (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2017)
In the terms of gender and sexuality, homosexual often has been accused as part of western culture, since Indonesian culture—and Islam—reputedly said it was aganist the western culture that uphold the freedom in many ways. Islam rejected the existence of homosexual. However there were some of them whom is born and raised in the islamic educational environments like Pesantren or islamic universities. This phenomena has become paradox from that thesis which lesbianism is not born from the womb of western culture. Even lesbianism itself is created by their own relational ideas. How the lesbians constructing religiousity over aganist the rigidity of textual commentation is the main question in this journal. And it has been founded that the lesbians feels their sexual orientation differences from early stage. That different kind of perception become their basis of behavior and interpreting life itself. Thus, their construction of religious commentary is not exactly similar with the majorities.